The Typologies of Islamic Thought: Mapping The Contemporary Intellectual Movements in Indonesia - Amin, Faizal (The Faculty of Islamic Theology and Humanities, UIN Walisongo Semarang, Indonesia, 2024)
The continuity and change of reformation ideas in the history of the Islamic intellectual movement necessitate a systematic categorization. This article endeavors to present a fresh framework for classifying Islamic thought, drawing inspiration from Fazlur Rahman’s categories of revivalist, classical modernist, neo-revivalist, and neo-modernist. More specifically, this article examines a reclassification of Islamic thought and elaborates on its implications for the contemporary historical narrative of the Islamic intellectual movement within the Indonesian context. By undertaking a comprehensive literature review and employing a descriptive methodology for data collection and analysis, this article found out eight categories or typologies characterizing contemporary Islamic intellectual movements in Indonesia: (1) the revivalist movement, (2) the classical modernist movement, (3) the neo-revivalist movement, (4) the neo-modernist movement, (5) the traditionalist movement, (6) the neo-traditionalist movement, (7) the post-modernist movement, and (8) the post-traditionalist movement. These typologies commence with the emergence of classical modernism juxtaposed against classical traditionalism as the turning point of the dialectical progression of Indonesian Islamic intellectualism. Each typology has undergone a transformative process and metamorphosis within a dynamic scientific dialectic.